Philippine National Police Initiatives in the Promotion of Peace and Order in Iligan City: Basis for Policy Recommendation - Galabin, Noel D.; Pallega, Rowell B.; Recapente, Marvin A. (Future Science / FSH-PH Publications, 2021)
This study aimed to determine the extent of the Philippine National Police Operation initiatives in the promotion of peace and order in Iligan City as a basis for policy recommendation. This study made use of a non-experimental quantitative research design utilizing the descriptive correlational technique, frequency count, percentage, mean and standard deviation, paired t-test, and Pearson-r correlations. The respondents exhibited a high level of response that the Philippine National Police always performed the police operational procedure initiatives in the promotion of peace and order. The finding showed that overall, there was a significant relationship between the frequency of implementation of police operations and the crime rate in terms of Index and non-index crime. Further studies are warranted.